Analisis Buku Guru Sejarah Kebudayaan Islam Kelas XI Terbitan Kemenag Kurikulum 2013 - Nuraidah, Syifa; Isana, Widiati; Sopianna, Pian (Lembaga Yasin AlSys, 2023)
A material from a book to be implemented in the teaching and learning process does require adjustments and also accuracy. The purpose of this study was to analyze the learning of Islamic Cultural History class XI Madrasah Aliyah Curriculum 2013 published by the Ministry of Religion in 2015. This study used library research, with a descriptive analysis method. The results of this study are that this book is presented in language that is easy to understand, concise, clear so that it can help teachers in the learning process. It is expected that educators educate with good quality and appropriate material so that they can improve the quality of education and achieve a learning goal.